Menyusuri Jalur Karier: Urgensi PGSD Sebagai Pintu Gerbang Menuju Kepegawaian PNS - Raudhatul Khasanah; Sam Rizqi Yunaenti; Sri Nurulita; Prihantini Prihantini (PT. ALHAFI BERKAH INDONESIA, 2023)
This article highlights the importance of the Department of Primary School Teacher Education (PGSD) as a basic tool for achieving career goals as a civil servant (PNS). The main focus is on how PGSD provides a strong educational foundation at the foundation level, develops teacher-student relationships to enhance ASN qualifications, and deals with transition years. This article highlights important aspects such as education, pedagogy, and character development in the PGSD curriculum. In addition, this article explains the challenges and opportunities faced by PGSD to meet the PNS qualification requirements while also recognizing the contribution of PGSD as an important component of Indonesian security. In this way, PGSD is seen as a strategic means to advance the PNS that not only meets the needs of basic education but also forms a more diverse generation.